Neutron-proton mass difference in nuclei in a relativistic harmonic quark model - Ferreira, P.Leal [UNESP] (Editrice Compositori Bologna, 1992)
The nuclear dependence of the neutron-proton mass difference is examined in a relativistic harmonic quark model with the assumption of a swelling of the individual nucleon originated by a decrease of the spring constant inside the nuclear medium. A decrease of the neutron-proton mass difference is obtained which is reasonably small and in the right direction to cope with the Nollen-Schiffer anomaly in mirror nuclei. © 1992 Società Italiana di Fisica.
Keywords: 12.40.Aa - Bag models and other phenomenological quark models; 21.10.Sf - Coulomb energies